Macrofoundations : exploring the situated nature of activity - W.J Steele, Christopher; R. Hannigan, Timothy; L Glaser, Vern; Toubiana, Madeline; Gehman, Joel (Research in the sociology of organizations ;, 2020)
This volume of Research in the Sociology of Organizations explores the institutional macro foundations of action, providing an array of insights into the constitutive and contextualizing powers of institutions, and an agenda for further exploration of these themes. The recent increase in attention to the micro foundations of institutions has been fruitful, but risks obscuring institutions' constitutive and contextualizing powers. This volume addresses this risk by focusing attention on how institutions shape the workings of the social and material world, our fundamental experiences, and the real-time unfolding of activity. It examines these institutional macro foundations, and provides rich accounts of the ways in which macro foundations shape and are shaped by micro-dynamics, in a co-constitutive interplay. This volume will be essential reading for management researchers, students, and all those interested in organization and organizational life.